Facing somatic symptom disorder in the emergency department. - Cozzi, Giorgio; Barbi, Egidio (J Paediatr Child Health, 2019)
Somatic symptom disorder is a condition in which a patient's subjective report of physical symptoms is associated with distress; disruption of day-to-day functioning; or disproportionate thoughts, feelings and behaviours regarding the symptoms, whether or not they are associated with an identified medical condition. While somatic symptom disorder affects a considerable proportion of children and adolescents presenting to the emergency department (ED), it has not been well investigated in the ED literature, nor is there much formal training in, or guidelines for, how to care for affected patients in the ED. The aim of this paper is to highlight the historical clues commonly reported by these patients in order to try to help the emergency physicians recognise patients affected by a somatic symptom disorder. Adolescent age, the presence of daily subjective symptoms presenting daily for weeks or months, a long medical history record, an extensive diagnostic workup and, most of all, disproportionate functional impairment related to the symptoms are all features strongly suggestive of this disorder. Emergency physicians should become used to taking advantage of these clues to formulate a positive diagnosis of somatic symptom disorder according to the most recent diagnostic criteria. Emergency physicians have the unique opportunity to contribute to the correct diagnosis and treatment of these patients and to have a positive impact on their prognosis.